Anticipation and Management of Coronary Heart Disease for Hajj Pilgrims - Vickry Wahidji (Universitas Negeri Gorontalo, 2022)
Background: The increasing number of Indonesian pilgrims yearly makes Indonesia the most significant country that sends pilgrims worldwide. But unfortunately, this is not accompanied by optimal health quality. One of the reasons is that most of these pilgrims are elderly and sometimes have suffered from degenerative diseases since they were in Indonesia.Contents: Coronary heart disease is the leading cause of death in developed and developing countries. The pathophysiology of coronary heart disease is closely related to lifestyle and a combination of risk factors such as hypertension, dyslipidemia, smoking, diabetes mellitus, age and family history.Conclusion: Early intervention on coronary heart disease's causes and precipitating factors can reduce morbidity and mortality, especially for pilgrims. For this reason, it is necessary to carry out good, and continuous collaboration between health workers and the pilgrims not only during the implementation of the pilgrimage in the holy land but has started when the pilgrims register as prospective pilgrims.